The efficacy and safety of Yupingfeng Powder with variation in the treatment of allergic rhinitis: Study protocol for a randomized, double-blind, placebo-controlled trial - Cheong, Pui Kuan; Ho, Tin Muk; Chan, Kam Leung; Lo, Cho Wing; Leung, Sin Bond; Hon, Kam Lun; Leung, Ka Chun; Siu, Tony Hon Chung; Song, Tian-He; Zhang, Hongwei; Ching, Jessica Yuet Ling; Chow, Tak Yee; et al. (Frontiers in Pharmacology, 2022)
Background: Allergic rhinitis (AR) is an upper airways chronic inflammatory disease mediated by IgE, which affects 10%–20% of the population. The mainstay for allergic rhinitis nowadays include steroids and antihistamines, but their effects are less than ideal. Many patients therefore seek Chinese medicine for treatment and Yupingfeng Powder is one of the most common formulae prescribed. In this study, we aim to investigate the efficacy and safety of Yupingfeng Powder with variation for the treatment of allergic rhinitis. Study design: This is a double-blind, randomized, placebo-controlled trial. A 2-week screening period will be implemented, and then eligible subjects with allergic rhinitis will receive interventions of either “Yupingfeng Powder with variation” granules or placebo granules for 8 weeks, followed by post treatment visits at weeks 12 and 16. The change in the Total Nasal Symptom Score (TNSS) will be used as the primary outcome. Discussion: This trail will evaluate the efficacy and safety of Yupingfeng Powder in treating allergic rhinitis. The study may provide the solid evidence of Yupingfeng Powder with variation can produce better clinical efficacy than the placebo granules. Trial registration:ClinicalTrials.gov, identifier NCT04976023.